Mechanical devices to compress the patient's chest in a state of sudden cardiac arrest - future or everyday life of emergency medicine - Rafał Czyż; Marcin Leśkiewicz; Izabela Czyż (Kazimierz Wielki University, 2018)
Providing high-quality chest compressions to patient in sudden cardiac arrest is a key action that should be taken by medical professionals as soon as possible after its recognition. Long-term keeping resuscitation, particularly chest compressions, can lead to fatigue rescuers which in turn may result in a decrease of the efficiency and quality of these treatments. Accordingly, it may be helpful to use commercially available medical devices for mechanical compression of the victim's chest. The aim of this study is to present selected devices for mechanical chest compressions of patient in cardiac arrest. Examples of such devices are: Lund University Cardiac Arrest System-LUCAS, AutoPulse Resuscitation System, Corpuls CPR, Life-stat CPR, Thumper CPR. Different between them are: mechanics of operation, construction, power source, size or also weight. Effectiveness and efficiency of all described devices have been confirmed by many scientific studies. Nevertheless, there are still no clear projects, which could become the basis for international organizations such as the European Resuscitation Council or American Heart Association to introduce these devices as a standard of patient care in the state of sudden cardiac arrest. Using of mechanical chest compression devices influence for providing the permanent quality of treatments, enables patient transport in cardiac arrest as well as relieves rescue team. It is necessary to conduct more studies which could confirm their effectiveness and also which could improve them.